Development of Professional Foreign Language Competence of Economics Students with MOOCs during the Pandemic - Artyom Dmitrievich Zubkov (MDPI AG, 2023)
Delving into the realm of massive open online courses (MOOCs), this investigation scrutinizes their role in enriching the professional language proficiency of economics undergraduates amidst a global coronavirus crisis. The research pivots on assessing the efficacy of MOOCs within higher learning curriculums while shedding light on the benefits and drawbacks of such an approach. The methodologies employed encompassed the analysis and interpretation of data derived from student polls and statistical analysis of yielded outcomes. The findings shed light on MOOCs as a potent instrument for honing language prowess and enriching the professional linguistic expertise of budding economists. The language experiment was participated in by a group of 34 students and their responses have been collated and interpreted as proposed guidelines for future reference. The participants notably appreciated the video-lecture format and exposure to native speakers' elocution. However, the study did not shy away from spotlighting certain limitations such as complexities in platform navigation and the difficulties of watching videos without subtitles. To optimize MOOC utilization, a series of recommendations were drawn up. These included offering choices to students, simplifying platform navigation, extending support during challenges, and bolstering speaking abilities. This exploration holds valuable insights not just for educators and students but also for academic institutions at large, offering hands-on data regarding the perks and pitfalls of employing MOOCs to cultivate professional foreign language competence within the field of economic education.